Culture and integration of Eurozone life insurance markets - Rubio-Misas, María (My University, 2022)
This paper provides the first evidence on how national culture conditions the integration of Eurozone life insurance markets. It analyzes seven markets over a sixteen-year sample period that includes the financial crisis. We focus on three cultural values, which are individualism, trust and hierarchy. The results indicate that collectivism culture increases cost and revenue performance and integration of Eurozone life insurance markets. Trust contributes to this integration, particularly in financial crisis, and egalitarian culture facilitates it in non-crisis time. Our findings are robust with tests designed to alleviate endogeneity concerns.
Keywords: Seguros - Europa - Congresos; National culture; Integration; Eurozone life insurance markets; Crisis